2005
DOI: 10.1007/s00374-005-0831-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil solution and extractable soil nitrogen response to climate change in two boreal forest ecosystems

Abstract: Several studies show that increases in soil temperature result in higher N mineralization rates in soils. It is, however, unclear if additional N is taken up by the vegetation or accumulates in the soil. To address this question two small, forested catchments in southern Norway were experimentally manipulated by increasing air temperature (+3°C in summer to +5°C in winter) and CO 2 concentrations (+200 ppmv) in one catchment (CO 2 T-T) and soil temperature (+3°C in summer to +5°C in winter) using heating cable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Resource allocation towards shoots in defoliated seedlings, or in seedlings under high nutrients and temperature supports the assumption that under these conditions assimilated carbon and light have become growth limiting factors (Tilman 1990). If global warming increases abundance of insect herbivores (Jepsen et al 2011), or nutrient availability by accelerating mineralization rates or enhancing atmospheric nitrogen deposition (Galloway et al 2004;Verburg 2005), the net effect in silver birch seedlings is to shift resource allocation toward shoot growth and away from root growth ( Fig. 4; Kleczewski et al 2012).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Resource allocation towards shoots in defoliated seedlings, or in seedlings under high nutrients and temperature supports the assumption that under these conditions assimilated carbon and light have become growth limiting factors (Tilman 1990). If global warming increases abundance of insect herbivores (Jepsen et al 2011), or nutrient availability by accelerating mineralization rates or enhancing atmospheric nitrogen deposition (Galloway et al 2004;Verburg 2005), the net effect in silver birch seedlings is to shift resource allocation toward shoot growth and away from root growth ( Fig. 4; Kleczewski et al 2012).…”
Section: Discussionmentioning
confidence: 76%
“…In fact, fertilization has enhanced the height and biomass growth of previously defoliated silver birch seedlings (Huttunen et al 2007). This is especially relevant because the broad impacts of global change frequently include increased atmospheric deposition of nitrogen (Galloway et al 2004) and accelerated mineralization rates of organic nitrogen in soil (Verburg 2005). On the other hand, defoliation may weaken the ability of roots to store resources as a result of increased carbon allocation to aboveground organs (Huttunen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4 Carbon capture policy; product substitution; changes in decomposition rates Kurz et al, 1995;Apps et al, 1999;Pederson, 2004;Spittlehouse, 2005;Verburg, 2005;Canadell & Raupach, 2008;Hennigar et al, 2008;Neilson et al, 2008;MacLean et al, 2010 Unmodified 4 Forest ecosystem change; timber supply fluctuation Dale et al, 2001;Schimel et al, 2001;Perez-Garcia et al, 2002;Stennes et al, 2005;DeLong et al, 2007;Spetic, 2009 Unmodified 5.1.3. 11 Timber supply fluctuation; global trade fluctuations Sohngen & Mendelsohn, 1998;Irland et al, 2001;Perez-Garcia et al, 2002;Lee & Lyon, 2004;Browne & Hunt, 2007;Kirilenko & Sedjo, 2007;Williamson et al, 2008;Jonsson, 2009 Peng & Apps, 1999;Volney & Fleming, 2000;Dale et al, 2001;Schimel et al, 2001;Perez-Garcia et al, 2002;Barrow et al, 2004;Spittlehouse, 2005;Bernier, 2007;Kirilenko & Sedjo, 2007;McKenney et al, 2007;Aitken et al, 2008;Hogg et al, 2008;Iverson et al, 2008;Lindenmayer & Noss, 2008;Flannigan et al, 2009 Unmodified 5.3.2. 27 Forest ecosystem change; timber supply fluctuation Irland, 1998;…”
Section: Discussionmentioning
confidence: 99%
“…Singh [38] found that N availability decreased by 12%-44% when the soil water content decreased. N is considered the most common limiting nutrient [39], and N is likely to enhance growth for many forests sites [40], by accelerating the leaching of other essential nutrients such as calcium, magnesium, and potassium [41]. To date, experiments indicate that an increase in N increases C sequestration [42,43].…”
Section: Precipitation and Evapotranspirationmentioning
confidence: 99%